EVALUATION OF AN INTEGRATED PEST MANAGEMENT SYSTEM FOR GREEN BEANS IN THE PROVINCE OF SUMAPAZ (CUNDINAMARCA) - PRADA, PEDRO C.; RODRÍGUEZ, ADELA; CARDONA, CÉSAR (Revista Colombiana de Entomología, 1993)
The greenhouse whitefly, Trialeurodes vaporariorum (Westewood), and the leafminer Liriomyza huidobrensis (Blanchard) are the two most important insect pests of snap beans in the Sumapaz province in Cundinamarca, Colombia. An IPM system for these insects was tested in a series of trials conducted in farmers' fields. Four initial replicated trials included the following treatments: "IPM" (a combination of cultural control practices with the application of a granular insecticide at planting and foliar insecticides applications at preestablished action levels); "Chemical" (rational application of foliar insecticides at preestablished action levels), and "Farmer's" (weekly application of foliar insecticides). Subsequently, treatments "IPM" and "Farmer's" were compared in four unreplicated trials conducted with farmers within a participatory research scheme. Whitefly and leafminer populations did not differ among treatments. In areas where the whítefly is the key pest, the IPM system resulted in 54% reduction in insecticide use and 18% reduction in costs, Participatory research demonstrated that implementation of an IPM system would permit a 62% reduction in insecticide use, with no losses in terms of yield or quality. In the San Bernardo area, where the Ieafminer is the key pest, results tend to indicate that it is virtually impossible to control this insect with traditional insecticides and that there is not yield increase when the insect is properly controlled with new insecticides. A possible IPM recommendation could be not to spray against the Leafminer.